Consumer Decision-Making in Car Purchases: Insights from a Logistic Regression Analysis - Simamora, Sandy J. H.; Ulkhaq, Mujiya; Handayani, Naniek Utami (LogicLink, 2025)
Indonesia, with its large population, presents significant consumer demand, particularly in the automotive sector. Consequently, numerous car brands actively invest and market their products within the country. Among the 36 car brands officially operating in Indonesia, Toyota has consistently dominated the market. This study specifically examines consumer perceptions and decision-making processes regarding Toyota car purchases using logistic regression analysis. It investigates the impact of perceived risk, price sensitivity, convenience, and customer satisfaction on consumers' purchasing choices. Using a quantitative approach, data were collected from Indonesian Toyota consumers through purposive sampling and analyzed using the logistic regression. The findings reveal that perceived risk and price significantly influence consumers' decisions to purchase Toyota cars, highlighting the importance for Toyota and other automotive brands to strategically manage risk perceptions and pricing policies to enhance consumer appeal and market share.